Policy Analysis and Decision-Making Framework for ESG Strategy Implementation at Pertamina's Refinery - Hartati, Sri; Hasyimi, Valid (Dinasti Publisher, 2026)
This study develops a policy analysis and decision-making framework for evaluating Environmental, Social, and Governance (ESG) strategy implementation in Pertamina's refinery business. It responds to the managerial tension between energy security, operational reliability, decarbonization, ESG credibility, and market confidence in a state-owned energy enterprise. A sequential mixed-methods single-case design was applied by combining stakeholder analysis, PESTLE analysis, Kepner-Tregoe problem diagnosis, ESG benchmarking, and Binary Analytic Hierarchy Process based on executive-level judgments. The findings show that the main issue is not the absence of ESG commitment but the weak alignment between ESG pillars and decision routines. Binary AHP supports adjusting the existing decision-making system with a priority score of 58.5% and a consistency ratio of 0.044. The study recommends an integrated ESG materiality matrix, carbon-adjusted capital allocation, an ESG digital dashboard, and phased governance integration to improve ESG strategy execution.